Perbandingan Produktivitas Excavator dan Dump Truk Sebelum dan Setelah Hujan - Anggraeny, Anggi Dwi; Muzdhalifa, Rencany Maura; Putra, I Nyoman Dita Pahang; Velantika, Griselda Junianda (Jurnal Talenta Sipil, 2025)
The construction project of the JLS Lot 3 Pantai Serang - Sumbersih is a concrete example of the government's efforts to enhance connectivity and infrastructure development in Indonesia. Heavy equipment such as excavators and dump trucks play a crucial role in enhancing efficiency and productivity in this project. Infrastructure development projects often encounter obstacles such as delays and high operational costs. Rain is one of the causes of those obstacles. One way to get a clear picture of the impact of rain is to conduct a comparative analysis of heavy equipment productivity before and after the rain. Evaluation of the decrease in productivity is necessary so that mitigation measures can be taken to minimize its impact on the project. This study aims to analyze and compare the productivity of excavators and dump trucks under conditions before and after rain on the JLS Lot 3 project. This study uses a quantitative method by analyzing primary data obtained through observation of the cycle time of excavators and dump trucks before and after rain in the field. The excavator's productivity before the rain was higher, at 1506.27 m3/day, compared to after the rain, at 854.33 m3/day. The productivity of the dump truck before the rain was also higher, at 259.60 m3/day, compared to after the rain, at 138.67 m3/day. The cause of the difference in productivity between the excavator and dump truck before and after the rain is the muddy and waterlogged field conditions, which lead to changes in the excavator's digging speed, per-cycle production, and the dump truck's rate while moving from the excavation site to the disposal site.